La cooperación entre la ue y el mercosur en el area científico-tecnológica - Rolandi, Maria Lis; Pinero, Fernando Julio (Faculdade de Ciências e Letras - Unesp - Araraquara., 2017)
In this article analyse itself process from co-operation between UE and Mercosur in thescience and technology area, because they are the result in the international scenery actual. However the rolls among both blocks be bared in mutual interest politics and economics, each other consider is it necessary to increase the commercials flood and existent inversions, it stimulating the significative economical setors for UE in report Mercosur, as Acuerdo Marco de Cooperación Interregional, among both blocks in 1995. So to speak, vital area for the fortification of American region it didn't go considerate in ditto Acuerdo, in worldwide context actual, the regional ambit is the connection that favour a co-operation more strait among blocks because of the negotiations have to increase the co-operation's programs, to intensify the commercial negotiations and to cure the regional problems.